Ciprofloxacin decreases the rate of ethanol elimination in humans. Issue 3 (1st March 1999) - Tillonen, J; Homann, N; Rautio, M; Jousimies-Somer, H; Salaspuro, M
Abstract : BACKGROUND: Extrahepatic ethanol metabolism is postulated to take place via microbial oxidation in the colon, mediated by aerobic and facultative anaerobic bacteria. AIMS: To evaluate the role of microbial ethanol oxidation in the total elimination rate of ethanol in humans by reducing gut flora with ciprofloxacin. METHODS: Ethanol was administered intravenously at the beginning and end of a one week period to eight male volunteers. Between ethanol doses volunteers received 750 mg ciprofloxacin twice daily. RESULTS: A highly significant (p=0.001) reduction in the ethanol elimination rate (EER) was detected after ciprofloxacin medication. Mean (SEM) EER was 107.0 (5.3) and 96.9 (4.8) mg/kg/h before and after ciprofloxacin, respectively. Faecal Enterobacteriaceae and Enterococcus sp. were totally absent after medication, and faecal acetaldehyde production capacity was significantly (p<0.05) decreased from 0.91 (0.15) to 0.39 (0.08) nmol/min/mg protein. Mean faecal alcohol dehydrogenase (ADH) activity was significantly (p<0.05) decreased after medication, but ciprofloxacin did not inhibit human hepatic ADH activity in vitro. CONCLUSIONS: Ciprofloxacin treatment decreased the ethanol elimination rate by 9.4%, with a concomitant decrease in intestinal aerobic and facultative anaerobic bacteria, faecal ADH activity, and acetaldehyde production. As ciprofloxacin has no effect on liver blood flow, hepatic ADH activity, or cytochrome CYP2E1 activity, these effects are probably caused by the reduction in intestinal flora.